Reactive Astrogliosis and Neuronal Functions of Astrocytes in Neurological Disorders - Mathure, Dyandevi; Kumar, Dileep; Ranpise, Hemantkumar; Awasthi, Rajendra (Indian Journal of Pharmaceutical Education and Research, 2024)
Astrocytes are the most abundant cells in the brain. Astrocytes take part in the absorption and recycling of neurotransmitters, inflammation, neuroenergetics, the release of gliotransmitters, the regulation of synaptic activity, the maintenance of the blood-brain barrier, and other processes. Astrocytes help to keep the central nervous system healthy and functioning properly. These cells are linked to the onset and progression of various neurodegenerative diseases. Recent research has revealed that these cells play a variety of active roles in both normal physiological homeostasis in the brain and neurodegeneration and disease. Astrocytes play a role in nervous system functions and the pathogenesis of Alzheimer's disease, Parkinson's disease, Huntington's disease, and amyotrophic lateral sclerosis. This review sheds light on the role of astrocytes in neuronal function and their mechanisms in synaptic transmission. We also summarized astrocytes' roles in various neurological diseases.
Keywords: Astrocytes; Alzheimer’s disease; Multiple sclerosis; Neurodegeneration; Parkinson’s; disease